Clonotype‐specific avidity influences the dynamics and hierarchy of virus‐specific regulatory and effector CD4+ T‐cell responses. Issue 4 (8th February 2014) - Liu, Jie; Cao, Shirley; Peppers, Gretchen; Kim, Sung‐Han; Graham, Barney S.
<x xml:space="preserve">Abstract</x> A key component of immunity against viruses, CD4+ T cells expand and differentiate into functional subsets upon primary infection, where effector (Teff) cells facilitate infection control and regulatory (Treg) cells mitigate immunopathology. After secondary infection, Teff cells mount a robust response from the memory pool. Here, we show that Treg‐cell responses are diminished upon secondary infection, and Treg‐cell response dynamics are associated more with T‐cell receptors (TCRs) repertoire and avidity than with epitope specificity. In the murine model, the IAbM209 epitope of respiratory syncytial virus is recognized by both CD4+ Treg and Teff cells, while the IAbM226 epitope is recognized almost exclusively by CD4+ Teff cells expressing high avidity TCR Vβ8.1/8.2 and dominating the CD4+ T‐cell response during primary and secondary infections. IAbM209‐Teff cells express relatively low avidity TCRs during early primary infection, but high avidity TCR Vβ7‐expressing IAbM209‐Teff cells emerge during the late phase, and become dominant after secondary infection. The emerging high avidity IAbM209‐Teff cells outcompete IAbM209‐Treg cells that share the same epitope, but have low avidity and are restricted to TCR Vβ2 and Vβ6 subpopulations. These data indicate that MHC‐peptide‐TCR interactions can produce different kinetic and functional profiles in CD4+ T‐cell populations even when responding to the same epitope.